Genesis Locations of the Costliest Atmospheric Rivers Impacting the Western United States - Hamish D. Prince; Peter B. Gibson; Michael J. DeFlorio; Thomas W. Corringham; Alison Cobb; Bin Guan; F. Martin Ralph; Duane E. Waliser (Geophysical Research Letters)
Abstract Atmospheric rivers (ARs) are responsible for the vast majority (∼88%) of flood damage in the Western U.S., an annual average of USD$1.1 billion. Here, using historical flood insurance data, we investigate the genesis characteristics of damaging ARs in the Western U.S.. ARs exceeding USD$20 million in damage (90th percentile), are shown to travel further across the Pacific Ocean, with median genesis locations 8°–27° further westward compared to typical ARs. Identifying regions of preferential genesis of damaging ARs elicit important implications for AR observation campaigns, highlighting distant regions not currently considered for AR reconnaissance. The genesis of damaging ARs is associated with elevated upper‐level zonal wind speeds along with deeper cyclonic anomalies, most pronounced for Washington and Oregon ARs. Linking AR dynamics and lifecycle characteristics to economic damage provides an opportunity for impact‐based forecasting of ARs prior to landfall, supporting efforts to mitigate extreme flood damages.